2015
DOI: 10.1097/j.pain.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

GABAAergic inhibition or dopamine denervation of the A11 hypothalamic nucleus induces trigeminal analgesia

Abstract: Descending pain-modulatory systems, either inhibitory or facilitatory, play a critical role in both acute and chronic pain. Compared with serotonin and norepinephrine, little is known about the function of dopamine (DA). We characterized the anatomical organization of descending DA pathways from hypothalamic A11 nuclei to the medullary dorsal horn (MDH) and investigated their role in trigeminal pain. Immunochemistry analysis reveals that A11 is a heterogeneous nucleus that contains at least 3 neuronal phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 44 publications
3
47
1
Order By: Relevance
“…These results indicate that A11 dopaminergic neurons are mainly regulated or modulated by a PV-lacking subgroup of GABAergic neurons. In addition, we did not detect any PV-IR cell bodies within the A11 region, in spite of several reports demonstrating that GABAergic neurons are present in this region [8,32,33]. Taken together, these results may indicate that non-PV-IR GABAergic neurons within or outside the A11 region regulate the activity of dopaminergic neurons of the A11 region.…”
Section: Parvalbumin-immunoreactive Fiberscontrasting
confidence: 81%
See 3 more Smart Citations
“…These results indicate that A11 dopaminergic neurons are mainly regulated or modulated by a PV-lacking subgroup of GABAergic neurons. In addition, we did not detect any PV-IR cell bodies within the A11 region, in spite of several reports demonstrating that GABAergic neurons are present in this region [8,32,33]. Taken together, these results may indicate that non-PV-IR GABAergic neurons within or outside the A11 region regulate the activity of dopaminergic neurons of the A11 region.…”
Section: Parvalbumin-immunoreactive Fiberscontrasting
confidence: 81%
“…Our study revealed that coronal sections from the rostral levels of the A11 region contained short PV-IR processes that varied in direction, while the caudal levels of the A11 region contained long PV-IR processes in the perpendicular direction, indicating that processes observed in the rostral aspects of A11 were extending in the rostro-caudal direction and processes observed in the caudal aspects were extending in the ventral-dorsal direction. These results indicate that the A11 region has morphological heterogeneity along the rostral-caudal axis and part of the functional heterogeneity suggested by previous studies [7,8] may attribute to the differential morphological property between the rostral and caudal aspect of the A11 region, such as different origin of inputs or differential connectivity of neurons in each subregion.…”
Section: Regional Heterogeneity Of the A11 Regionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this area, several enzymatic pathways for production of steroids and neurosteroids exist. These chemicals induce the expression of GABA‐A, NMDA and P2X receptors in spinal cord and play a pivotal role in pain modulation . The wide distribution of neurosteroids in spinal cord dorsal horn also supports this hypothesis .…”
Section: Introductionmentioning
confidence: 74%